Case Report: Cardiac Multiple Thrombus and Pulmonary Embolism Associated With Mycoplasma Pneumonia Infection in a Child - Tongqiang Zhang; Jiafeng Zheng; Hongbo Wang; Yongsheng Xu; Jing Ning; Chunquan Cai (Frontiers in Pediatrics, 2022)
Mycoplasma pneumoniae (MP) is a common pathogen of lower respiratory tract infection in children and adolescents. Some patients with MP infection are self-limiting, while with the increase of severe or refractory Mycoplasma pneumoniae pneumonia (MPP) in recent years, there is a great increase in reports of thromboembolism in multiple organs, including lung, brain, spleen, and peripheral arteries. Cardiac multiple thrombi and pulmonary embolism associated with MP infection have not been reported. The most effective treatment option for cardiac thrombus was surgical resection for fear of thrombus detachment and causing new thromboembolism. Herein, we present a patient with cardiac multiple thrombi and pulmonary embolism in MPP for the first time. In our case, the child recovered after conservative medical treatment, which provides a therapeutic option for children with cardiac multiple thrombi.